SOSIALISASI BANK DIGITAL UNTUK KEGIATAN PRODUKTIF MANAJEMEN KEUANGAN DI GEREJA GBT KRISPASIH KEDIRI - Hanggondosari, Sri Utami; Riyanah, Riyanah; Kusuma, Hendra; Mardijani, Prastiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Pawyatan Daha, 2024)
Abstract This community service aims to introduce digital banking and usage techniques for productive financial management activities at the GBT Krispasih Church in Kediri. The target is to increase knowledge and change the way participants view Digital Banking in practice. The activity was carried out on April 16 2024. After discussions with the Church Council management community, it was agreed that the activity would begin with an explanation of Digital Bank, its uses, as well as identification of positive and negative impacts through a direct question and answer process with participants. This activity ran smoothly and according to target. There were 29 participants who attended. There are some who are familiar with online transactions but don't have a business. The result of this community service is that participants admit that they have become clearer about Digital Banks and Conventional Banks, digital transactions, uses and techniques to avoid negative things and the characteristics of digital fraud. So it can be concluded that participants have increased their abilities regarding Digital Banking and its practical use for productive things.